POTENSI SERTIFIKASI HALAL DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Deviana Yuanitasari; Helitha Novianty Muchtar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: Countries in various parts of the world are currently very concerned about the importance of an adequate standard of living with a sense of safety in the use of a product. Product quality is determined based on a standard of eligibility with evidence of a packaging label. The label is a guideline for determining the level of a product used. ASEAN as a single market and a unified production base, with free flow of goods, services, production factors, investment, and capital, as well as the elimination of tariffs for trade between ASEAN countries, is a reality that ASEAN countries, especially Indonesia, cannot negotiate. The movement of goods in ASEAN in free trade causes the Muslim community in Indonesia and other ASEAN countries to question the halalness of products that enter from abroad, therefore. This article aims to discuss the potential for halal certification in the scope of development of the ASEAN economic community market. This research method is normative juridical and analytical descriptive. The results show that halal certification for food products must be carried out, by taking into account the uniformity of requirements, labels, and registration in one application for registration of halal certification in ASEAN Countries ASEAN national cooperation related to halal certification such as the establishment of institutions (regional halal accreditation boards), the establishment of a single registration system. application, uniformity of requirements, halal standards, regional certification, the establishment of regulations, and approval in the field of halal certification are the right solutions today to provide convenience for business actors while ensuring the safety of halal products in Indonesia.